Integrating the edges: University of Pretoria's neighbourhood anchor strategy. Issue 5 (3rd September 2018) - Hendricks, Denver; Flaherty, Jaime
ABSTRACT: The traditionally inward focus of many higher education institutions in both the United States (US) and South Africa has often failed to address important urban issues beyond the university gates, confining most student and academic activity to the campus. Universities can create social change not just through their primary teaching and research functions, but also through the promotion of integration on and around their campuses. In addition, place-based activities that improve neighbourhoods can help to attract students and staff, as well as new businesses and services. In particular, they can foster the influx of young professionals and families seeking to help build open, safe, vibrant and diverse communities, which may represent a new model for South African socio-economic integration beyond the 'gated' framework. Accordingly, the University of Pretoria (UP) has sought to lead an urban renewal and social transformation project around its Hatfield campus.